The surrounds : urban life within and beyond capture - Simone, A. M. (Abdou Maliqalim) (Theory in forms., 2022)
"AbdouMaliq Simone's The Surrounds brings abolitionist theorizing to the untapped potentialities of contemporary urbanization in the so-called Global South. The book mobilizes various developments in critical Black thought to conceptualize urban spaces that have exceeded or subverted their design in response to individual or collective use. Composed as an interweaving of ethnography, literary reflection, theory, and poetics, The Surrounds reads against the grain of some common assumptions: that memory is critical to freedom; that alternative worlds are possible, and that rebellion is redeemed by the creation of such worlds. As an intersection of urban theory, Black study, and decolonial and Islamic thought, the book poses the surrounds as those spaces beyond capture, not immune from it, not free of it, but rather something aside it as a locus of continuous rebellion. The surrounds introduce space and spaciousness to the regimes of computation that seek to precisely define the parameters through which people, built environments, and the more than human relate with each other. Although situated in multi-sited ethnography and urban studies, The Surrounds speaks to a much wider range of Black critical theory and will be of interest across global Black studies"--